Moderation of Housing-Related Factors on Psychological Capital–Job Embeddedness Association - Ren, Tianzhou; Jin, Xizan; Rafiq, Muhammad; Chin, Tachia (Frontiers in Psychology, 2019)
This study identified three critical housing-related factors as moderators of the relationships between employees’ psychological capital (PsyCap) and job embeddedness in China’s entrepreneurial environment. The hypotheses were tested with multiple hierarchical regressions modeling, using the data collected from 312 employees in manufacturing organizations. The results demonstrated that housing-related factors (i.e., home ownership, housing price satisfaction, and contributions to housing funds) moderate the relationships between employees’ PsyCap and job embeddedness. Specifically, these relationships were stronger when the housing-related factors were high. Such results contribute to the psychological capital and job embeddedness literatures by incorporating housing as an extrinsic life-aspect factor that might affect employees’ psychological state and thus their retention in works. Implications for the organization policies and directions for future studies were discussed.